THE INFLUENCE OF JOB SATISFACTION AND WORKLOAD ON EMPLOYEE PERFORMANCE AT PT ANGKASA AVIASI SERVIS BRANCH PEKANBARU - Andi Hardiyanti Maulana; Randico Amanda; Sumardin (PENANOMICS: International Journal of Economics, 2023)
The purpose of this study was to determine the effect of job satisfaction and workload on employee performance at PT Angkasa Aviasi Servis Pekanbaru Branch. Population and sample as many as 35 people. The measurement tool used is a questionnaire containing 70 statements consisting of 35 job satisfaction statements, 15 workload statements and 20 employee performance statements. Data analysis using the t test, F test, and the coefficient of determination. The results of the job satisfaction t-test study obtained sig 0.565 > 0.05, so satisfaction has no significant effect on employee performance, while workload has a sig 0.000 <0.05, so workload has a significant effect on employee performance. The results of the F test obtained a value of 0.000 <0.05 so it can be concluded that job satisfaction and workload have a significant effect on employee performance.